Inflammatory markers are associated with cardiac autonomic dysfunction in recent-onset type 2 diabetes. Issue 1 (1st August 2016) - Herder, Christian; Schamarek, Imke; Nowotny, Bettina; Carstensen-Kirberg, Maren; Straßburger, Klaus; Nowotny, Peter; Kannenberg, Julia M; Strom, Alexander; Püttgen, Sonja; Müssig, Karsten; Szendroedi, Julia; Roden, Michael; et al.
Abstract : Objective: Cardiovascular autonomic neuropathy is a common but underestimated diabetes-related disorder. Associations between cardiovascular autonomic dysfunction and subclinical inflammation, both risk factors of diabetic comorbidities and mortality, have been proposed in non-diabetic populations, while data for type 1 and type 2 diabetes are conflicting. Our aim was to investigate associations between inflammation-related biomarkers and cardiac autonomic dysfunction in patients with diabetes. Methods: We characterised the associations between seven biomarkers of subclinical inflammation and cardiac autonomic dysfunction based on heart rate variability and cardiovascular autonomic reflex tests (CARTs) in 161 individuals with type 1 and 352 individuals with type 2 diabetes (time since diagnosis of diabetes <1 year). Analyses were adjusted for age, sex, anthropometric, metabolic and lifestyle factors, medication and cardiovascular comorbidities. Results: In individuals with type 2 diabetes, higher serum interleukin (IL)-18 was associated with lower vagal activity (p≤0.015 for association with CARTs), whereas higher levels of total and high-molecular-weight adiponectin showed associations with very low frequency power, an indicator of reduced sympathetic activity (p≤0.014). Higher levels of soluble intercellular adhesion molecule-1 were associated with indicators of both lower vagal (p=0.025) and sympathetic (p=0.008) tone, soluble E-selectin with one indicator of lower vagal activity (p=0.047). Serum C-reactive protein and IL-6 were also related to cardiac autonomic dysfunction, but these associations were explained by confounding factors. No consistent associations were found in individuals with type 1 diabetes. Conclusions: Biomarkers of inflammation were differentially associated with diminished cardiac autonomic dysfunction in recent-onset type 2 diabetes.